Editorial: ePortfolio practice for emerging, connecting, and sustaining pedagogies - Sankey, Michael; Paterson, Terrie; Miller, Allison (Journal of University Teaching and Learning Practice, 2025)
With ePortfolio practice now being well over 20 years old and, to a great extent, mainstreamed within the Australasian higher education sector (indeed globally), it is timely to reflect on current pedagogical trends within this practice. The focus of each of the articles in this special edition does just that, but with a special focus on emerging practices, connecting students to their future professions, whilst looking to sustain consistent institutional practices. The 9 articles within this edition do not try and justify the use of ePortfolio, as that case has well and truly been prosecuted and won over the years, rather, now that it is established, this frees us to look at more nuanced issues, such as student well-being, the application of different pedagogical theories, different educational design processes, and supporting users through different communities of practice within the sector. Notwithstanding, with the advent of generative AI over the last two years and a renewed focus on the use of ePortfolio to enhance the opportunity for program-wide assessment, we top and tail this edition by putting the student at the centre of this practice. More particularly, through the notion of well-being and the pedagogy of care, how these concepts can lead to a more satisfying outcome for all concerned.